Tetra-mu-acetato-kappa O-8:O `-bis{[4-methyl-N-(4-methylphenyl)pyridin-2-amine-kappa N-1]copper(II)} - Fairuz, Z.A.; Aiyub, Z.; Abdullah, Z.; Ng, S.W.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The title complex, [Cu-2(CH3COO)(4)(C13H14N2)(2)], features a binuclear molecule, which lies about a crystallographic centre of inversion; the four acetate ions each bridge a pair of Cu-II atoms. The coordination of the metal atom is distorted octahedral within a donor set defined by four O atoms, the heterocyclic N atom and the second Cu atom. The pyridine ring is twisted with respect to the tolyl ring and forms a dihedral angle of 35.34(9)degrees. A bifurcated N-H center dot center dot center dot(O,O) hydrogen bond is present, linking the amine group to two carboxylate O atoms derived from different acetate ions. In the crystal, C-H center dot center dot center dot pi interactions link molecules into a supramolecular array in the bc plane.